THERMODYNAMIC PROPERTIES OF NA2SO4(AQ) ABOVE 200°C - Pitzer K.S.; Das B. (My University, 1998)
In 1988 Pabalan and Pitzer published in this journal two equations valid for various thermodynamic functions for Na2SO4(aq) at temperatures to 300°C. One was based on their measurements at 200 bars pressure, with other data at low temperatures converted to that pressure. The second equation was for 1 bar to 100°C and Psat at higher temperatures. At temperatures below 200°C, the effect of pressure was reasonably well known from volumetric measurements and other data, but above 200°C there were no volumetric data available. Thus, the activity and osmotic coefficients reported for Psat above 200°C were based on estimates of the effect of the (200 bar-Psat) pressure difference. Recent volumetric measurements to 300°C of s il et al 1996>, s il et al 1997>) yield accurate values for this pressure effect, which are presented here. Comparisons show that the estimates of 1988 were good and that the activity coefficients of 1988 are accurate within the uncertainties of various other input data.